Artificial Intelligence In The Indian Judiciary: Current Applications And Future Prospects (Journal of Namibian Studies : History Politics Culture, 2023)
The Indian judicial system is grappling with a significant challenge due to the exponential growth in population over the decades coupled with a shortage of judges. As a consequence, there has been a substantial increase in the number of pending cases, and inefficiencies in court processes have become more pronounced. This paper explores the potential of Artificial Intelligence in addressing the challenges faced by the Indian judicial system. It thoroughly examines the existing use of Artificial Intelligence by the judicial system, including systems like SUPACE, SUVAAS, and E-Filling. Furthermore, the article explores the potential applications of artificial intelligence in the Indian judicial system and the use of artificial intelligence by judicial systems around the world. It also scrutinizes the regulatory approaches towards Artificial Intelligence followed by developed countries and the Indian authorities. Additionally, it discusses the future challenges associated with the adoption of Artificial Intelligence in the legal sector and emphasizes the important factors to consider when implementing Artificial Intelligence in the judicial system.